A Compartmental Pharmacokinetic Evaluation of Long‐Acting Rilpivirine in HIV‐Negative Volunteers for Pre‐Exposure Prophylaxis. Issue 3 (26th May 2014) - Jackson, A G A; Else, L J; Mesquita, P M M; Egan, D; Back, D J; Karolia, Z; Ringner‐Nackter, L; Higgs, C J; Herold, B C; Gazzard, B G; Boffito, M
<x xml:space="preserve">Abstract</x> Rilpivirine long‐acting (RPV‐LA) is a parenteral formulation enabling prolonged plasma exposure. We explored its multiple‐compartment pharmacokinetics (PK) after a single dose, for pre‐exposure prophylaxis. Sixty‐six HIV‐negative volunteers were enrolled: women received an intramuscular dose of 300, 600, or 1, 200 mg, with plasma and genital levels measured to 84 days postdose; men receiving 600 mg had similar PK determined in plasma and rectum. Ex vivo antiviral activity of cervicovaginal lavage (CVL) was also assessed. After a single dose, RPV concentrations peaked at days 6–8 and were present in plasma and genital‐tract fluid to day 84. Vaginal and male rectal tissue levels matched those in plasma. At the 1, 200 mg dose, CVL showed greater antiviral activity, above baseline, at days 28 and 56. All doses were well tolerated. All doses gave prolonged plasma and genital‐tract rilpivirine exposure. PK and viral inhibition of repeated doses will be important in further dose selection. Clinical Pharmacology & Therapeutics (2014); 96 3, 314–323. advance online publication 25 June 2014. doi:10.1038/clpt.2014.118